TINJAUAN YURIDIS KEABSAHAN RAPAT UMUM PEMEGANG SAHAM BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 607 K/PDT/2011 - RIBKA ANGELIA M SIANIPAR (PREMISE LAW JURNAL, 2013)
ABSTRACT   Share Holder General Meeting (RUPS) is one of the organs of a company with the authority which is not given to the other organs of company. Share Holder General Meeting is the place where the share holders get together to discuss everything related to the company whose implementation refers to the Statute of Company as long as it is not in opposition with the provision of Law No. 40/2007 on Limited Liability Company and/or if it is not regulated in the Statute of Company, the provisions refer to Law No. 40/2007. Sometimes, one or several of the share holders does not want to attend an Extraordinary Share Holder General Meeting because they do not agree with the agenda of meeting to be discussed in the Extraordinary Share Holder General Meeting. Especially, if all of the share holders are the heirs of one of the other share holders who have passed away. This may occur due to family conflict or conflict of interest between the heirs whoa re also the share holders of the same company. Keywords: Share Holder General Meeting, Limited Liability Company, Statute, Share